2019
DOI: 10.3390/molecules24234337
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between the Water Solubility and Secondary Structure of Tilapia-Soybean Protein Co-Precipitates

Abstract: The secondary structure of a protein has been identified to be a crucial indicator that governs its water solubility. Tilapia protein isolate (TPI), soybean protein isolate (SPI), and tilapia-soybean protein co-precipitates (TSPC3:1, TSPC2:1, TSPC1:1, TSPC1:2, and TSPC1:3) were prepared by mixing tilapia meat and soybean meal at different mass ratios. The results demonstrated that the water solubility of TSPCs was significantly greater than that of TPI (p <0.05). The changes in ultraviolet–visible and near-ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 52 publications
8
16
0
Order By: Relevance
“…Also, Tan et al identified the significant relationship between protein solubility and ordered secondary structure content such as helix and beta sheets (Tan et al 2019). They found large helix and beta sheet content within the most soluble proteins (Tan et al 2019). Thus, our results, which suggest that ordered secondary structures such as helix and beta sheets, as well as a larger fraction of solvent exposed residues with higher relative solvent accessibility cutoffs, contribute to protein solubility, correlate well with experimental findings.…”
Section: Effect Of Additional Biological Features On Dsressol Performancesupporting
confidence: 88%
See 2 more Smart Citations
“…Also, Tan et al identified the significant relationship between protein solubility and ordered secondary structure content such as helix and beta sheets (Tan et al 2019). They found large helix and beta sheet content within the most soluble proteins (Tan et al 2019). Thus, our results, which suggest that ordered secondary structures such as helix and beta sheets, as well as a larger fraction of solvent exposed residues with higher relative solvent accessibility cutoffs, contribute to protein solubility, correlate well with experimental findings.…”
Section: Effect Of Additional Biological Features On Dsressol Performancesupporting
confidence: 88%
“…identified the significant relationship between protein solubility and ordered secondary structure content such as helix and beta sheets [49]. They found large helix and beta sheet content within the most soluble proteins [49].…”
Section: Effect Of Additional Biological Features On Dsressol Performancementioning
confidence: 98%
See 1 more Smart Citation
“…It can be seen that the main components of serum are protein, lipid and nucleic acids. The amide I protein (1700-1600cm −1 ) band mainly originated from the α-helix structure at 1646cm -1 ( 28 ). The amide II protein (1560-1500cm −1 ) band mainly originated from the N-H functional group at 1542cm -1 ( 29 ).…”
Section: Resultsmentioning
confidence: 99%
“…The WSI of various processed ingredients was highest among the high protein ingredients like whey protein (87.62±0.01%) and skimmed milk powder (83.00±0.20%) followed by popped amaranth flour (48.62±0.01%), malted green gram (39.38±0.60%) while least per cent water solubility was observed in flaxseed (23.66± 0.77%). This was because the solubility in water is contributed by protein structure in protein rich product [30]. Developed enteral formulae were observed to have 62.66±0.20 per cent, 51.00±0.12 per cent and 49.66±0.23 per cent in HPEF, BEF and HEEF respectively.…”
Section: Respectivelymentioning
confidence: 99%